Environmental management prospects of industrial area: A case study on Mcie, Indonesia - Sjaifuddin Sjaifuddin (Verslas: Teorija ir praktika / Business: Theory and Practice, 2018)
In addition to promote economic growth, industrialization had caused negative impacts on the environment. It was required a lot of efforts to overcome negative impacts, although the results were still not as expected. Starting from this condition this research aimed to design an environmental management prospect of Modern Cikande Industrial Estate (MCIE) in Serang, Banten Province, Indonesia. Environmental management prospect designed using a prospective analysis. This technique used to explore various possibilities in the future in environmental management of MCIE based on eco-industrial parks (EIPs). The analysis showed that there were 5 (five) key factors determine the success of environmental management of MCIE: pollution control, investment security, availability of infrastructure, industrial tourism, and competitiveness of industry. The most implementable scenario in MCIE environmental management in the future was the new urbanism. This scenario oriented on the long term balance between economic growth and environmental protection.
Keywords: O13; Q57; 650; environmental management prospects; industrialization; prospective analysis; eco-industrial parks; key factors; new urbanism